Relationship between urinary albumin and serum soluble fms-like tyrosine kinase 1 (sFlt-1) in normal pregnancy - Yoshimatsu, Jun; Matsumoto, Harunobu; Goto, Kiyomi; Shimano, Masako; Narahara, Hisashi; Miyakawa, Isao (European journal of obstetrics & gynecology and reproductive biology, 2006)
To investigate if the circulating level of soluble fms-like tyrosine kinase 1 (sFlt-1) and vascular endothelial growth factor (VEGF) correlates with urinary albumin excretion in normal pregnancy. Serum specimens and 24 h urine collections were requested from normal pregnant women at 28–30 weeks of gestation and the following laboratory tests were performed: serum creatinine, urinary protein, urinary albumin and creatinine clearance. For the present study, 117 normal pregnant women were selected as subjects. Subjects’ serum was tested to determine sFlt-1 and VEGF concentrations by ELISA. The correlation between sFlt-1 or VEGF concentrations in the serum and renal laboratory variables were analyzed. Simple regression was used to evaluate the correlations. A significant association was noted between serum sFlt-1 concentration and urinary albumin excretion ( r = 0.68; P < .0001). Similarly, a significant association was noted between serum VEGF concentration and urinary albumin excretion ( r = −0.39; P < .0001). Other urinary variables showed no correlations with either sFlt-1 or VEGF. Even in normal pregnancy, albumin excretion is affected by an increase in placentally derived sFlt-1. If the sFlt-1 level is kept within normal range, only glomerular endothelial cells are affected and this phenomenon does not spread to the endothelial cells of a whole body.